Rucaparib maintenance treatment for recurrent ovarian carcinoma: the effects of progression‐free interval and prior therapies on efficacy and safety in the randomized phase III trial ARIEL3. Issue 7 (July 2021) - Clamp, Andrew R; Lorusso, Domenica; Oza, Amit M; Aghajanian, Carol; Oaknin, Ana; Dean, Andrew; Colombo, Nicoletta; Weberpals, Johanne I; Scambia, Giovanni; Leary, Alexandra; Holloway, Robert W; Gancedo, Margarita Amenedo; et al.
ABSTRACT : Introduction : In ARIEL3 (NCT01968213), the poly(adenosine diphosphate‐ribose) polymerase inhibitor rucaparib significantly improved progression‐free survival versus placebo regardless of biomarker status when used as maintenance treatment for recurrent ovarian cancer. The aim of the current analyses was to evaluate the efficacy and safety of rucaparib in subgroups based on progression‐free interval following penultimate platinum, number of prior chemotherapies, and prior use of bevacizumab. Methods : Patients were randomized 2:1 to rucaparib 600 mg twice daily or placebo. Within subgroups, progression‐free survival was assessed in prespecified, nested cohorts: BRCA ‐mutant, homologous recombination deficient ( BRCA ‐mutant or wild‐type BRCA /high genomic loss of heterozygosity), and the intent‐to‐treat population. Results : In the intent‐to‐treat population, median investigator‐assessed progression‐free survival was 8.2 months with rucaparib versus 4.1 months with placebo (n=151 vs n=76; HR 0.33, 95% CI 0.24 to 0.46, p<0.0001) for patients with progression‐free interval 6 to ≤12 months, and 13.6 versus 5.6 months (n=224 vs n=113; HR 0.39, 95% CI 0.30 to 0.52, p<0.0001) for those with progression‐free interval >12 months. Median progression‐free survival was 10.4 versus 5.4 months (n=231 vs n=124; HR 0.42, 95% CI 0.32 to 0.54, p<0.0001) for patients who had received two prior chemotherapies, and 11.1 versus 5.3 months (n=144 vs n=65; HR 0.28, 95% CI 0.19 to 0.41, p<0.0001) for those who had received ≥3 prior chemotherapies. Median progression‐free survival was 10.3 versus 5.4 months (n=83 vs n=43; HR 0.42, 95% CI 0.26 to 0.68, p=0.0004) for patients who had received prior bevacizumab, and 10.9 versus 5.4 months (n=292 vs n=146; HR 0.35, 95% CI 0.28 to 0.45, p<0.0001) for those who had not. Across subgroups, median progression‐free survival was also significantly longer with rucaparib versus placebo in the BRCA ‐mutant and homologous recombination deficient cohorts. Safety was consistent across subgroups. Conclusions : Rucaparib maintenance treatment significantly improved progression‐free survival versus placebo irrespective of progression‐free interval following penultimate platinum, number of lines of prior chemotherapy, and previous use of bevacizumab.